Investigating the Molecular miRNAs as Biomarkers of Type 2 Diabetes - Salman Sadeghzadeh; Mahmood Dehghani Ashkezari; Seyed Morteza Seifati; Mohammad Yahya Vahidi Mehrjardi; Sara Sadeghzadeh (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2022)
Introduction: Biomarkers would significantly improve the early detection of the disease and identification of individuals at risk of emerging complications. Diabetes mellitus is a group of diverse and complex metabolic disorders. Both type 1 diabetes (T1D) and type 2 diabetes (T2D) mellitus are associated with distinct alterations in the profile of MicroRNAs (miRNAs) in the blood, which are sometimes detectable several years before the disease manifests. Lately, considerable attention has been paid to the role of miRNAs as biomarkers for T2D. The aim of this study was to review the expression of different miRNAs in pre-diabetic (per-T2D), T2D and healthy groups. Conclusion After evaluating several articles, including main articles, meta-analysis and review studies, it was found that the expression of micRNAs was statistically different in healthy, pre-T2D and T2D groups. In addition, the expression of specific miRNAs is useful in preventing disease and modifying gene structure. This study indicated that the plasma expression level of miRNAs could be considered as a non-invasive and fast tool for the separation of pre-T2D individuals from their healthy counterparts.